ENHANCEMENT OF COMMUNITY WELFARE IN TOURISM AREAS THROUGH COOPERATIVE INVOLVEMENT: ANALYSIS OF DOMINANT FACTORS WITH EDUCATION AS MODERATING VARIABLE - Suwendra, I Wayan; Irwansyah, M. Rudi; Meitriana, Made Ary; Yakob, Noor Azudin (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2025)
This research aims to analyze dominant factors affecting community welfare enhancement through tourism cooperative involvement in Buleleng Regency, with particular emphasis on education's moderating role. A quantitative approach employed structural equation modeling (SEM) with SmartPLS 4.0, analyzing data from 180 tourism cooperative members selected through stratified proportional random sampling across three tourism areas. The enhanced model demonstrates excellent fit. Access to capital emerged as the dominant factor, followed by human resource capacity and marketing networks. Education significantly moderates the relationships between access to capital and community welfare and between human resource capacity and community welfare. The moderation analysis revealed that higher education levels enhance the effectiveness of capital access and skill development interventions. The study establishes the "Cooperative-Mediated Community Welfare Model with Educational Enhancement" (CMCW-EE), demonstrating that education amplifies the effectiveness of resource-based interventions while having minimal impact on relational factors. These findings provide crucial insights for designing targeted interventions in community-based tourism development.